Proteus syndrome – a case report - Materna-Kiryluk, Anna; Lasko, Grażyna; Badura, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
A 3-year-old boy with Proteus syndrome is presented. The child demonstrates a minimal asymmetry of the body and typical skin lesions (moccasin lesion), which the diagnosis to be made.